A comprehensive study of fuel composition, combustion and soot nanostructure characteristics of a diesel/light hydrocarbons premixed charge compression ignition engine. (15th August 2020) - Chen, Hanyu; Wang, Xi; Pan, Zhixiang
Highlights: Light hydrocarbons exhibits short carbon chain and high volatility. Light hydrocarbons PCCI engine represents higher THC and lower CO and NOx emissions. Soot aggregate of light hydrocarbons PCCI engine exhibits more sparse and chain-like. Primary particles in light hydrocarbons PCCI engine represent more ordered graphitic and fullerenic nanostructure. Abstract: The present research concentrates on the fuel properties and engine operating conditions on combustion and emission characteristics especially for morphology and nano-structure of a light hydrocarbons PCCI engine. The experiments were conducted by using gas chromatography-mass spectrometry, thermogravimetric analysis and high-resolution transmission electron microscopy. Additionally, the performance, combustion and gaseous pollutant emissions characteristics were also performed. The results indicate that the carbon chain length of main compounds in light hydrocarbons sample is shorter and the volatile matter content is higher. TG/DTG curves of light hydrocarbons move to a lower temperature region compared to diesel, which is due to lower decomposition temperature and higher volatility of light hydrocarbons. The performance characteristics show that BSFC is higher and BTE is lower in light hydrocarbons PCCI engine compared to conventional diesel engine. The combustion and emission characteristics show that the in-cylinder peak pressure of light hydrocarbons PCCI engine is reduced by 18.1%, and the pressure rise rate and heat release rate present a consistent variation trend compared to conventional diesel engine. Light hydrocarbons PCCI engine exhibits higher THC emission with respect to different engine load, while CO and NOx emissions are lower. Compared with conventional diesel engine, the soot aggregate of light hydrocarbons PCCI engine exhibits more sparse, and it appears more chain-like. Additionally, the primary particles in light hydrocarbons PCCI engine represent more ordered graphitic and fullerenic nanostructure.